PRODUKTIVITAS KERJA PEGAWAI PADA KOMANDO DISTRIK MILITER (KODIM) 0303 KOTA DUMAI - HASIBUAN, MALIANNA; SD, Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Resident of a State , in essence a very important resource for development , one of the ways the organization in improving its mission through the work productivity of employees in the organization in which labor productivity is the result or a person's overall success rate for a certain period in the task are some constraints on employee productivity District Military Command ( Kodim ) 0303 Dumai as the persistence of the employees who have not been able to operate a computer at work , and persistence of the employees who are not on time .The concept of the theory used L.mathis (2002 ) uses the measurement of productivity indicators: Quantity Work , Work Quality , Utilization Time , Cooperation , Creativity . By measuring the productivity of the employees KODIM 0303 Dumai and to know about productivity in completing tasks that have been given and identify factors - factors that affect and hamper productivity. Departing from the author is interested in researching the problem and seeks to provide solutions for improving employee productivity KODIM Dumai .The results of this study showed that employee productivity District Military Command ( Kodim ) 0303 in terms of completing a given task is not maximized in the work , it is still the complaints of employers and jobs that have not been completed on timeKeywords : Work Productivity, Employe, KODIM